1984
DOI: 10.1037/0022-0663.76.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Toward a theory of cognitive aptitude for learning from instruction.

Abstract: This article reviews progress toward the development of a cognitive theory of aptitude for learning and presents descriptive and prescriptive goals for aptitude theories. Preliminary hypotheses about the nature of cognitive processes in aptitude for learning from instruction are reviewed. Twelve constituent points of the descriptive theory are presented. Some of these points are summary conclusions of much prior research, whereas others are less well supported at present. However, all contribute to the effort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
146
0
4

Year Published

1993
1993
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(162 citation statements)
references
References 30 publications
(42 reference statements)
12
146
0
4
Order By: Relevance
“…Research in educational settings finds that low-g learners require highly structured, detailed, concrete, and "contextualized" instruction that omits no intermediate steps, but that such "complete" instruction is actually dysfunctional for high-g individuals. The latter easily fill gaps in instruction on their own and benefit most from abstract, self-directed, incomplete instruction that allows them to assemble new knowledge and reassemble old knowledge in idiosyncratic ways (Snow & Lohman, 1984).…”
Section: Focus On Specific Training Not Broad Education When Time Amentioning
confidence: 99%
“…Research in educational settings finds that low-g learners require highly structured, detailed, concrete, and "contextualized" instruction that omits no intermediate steps, but that such "complete" instruction is actually dysfunctional for high-g individuals. The latter easily fill gaps in instruction on their own and benefit most from abstract, self-directed, incomplete instruction that allows them to assemble new knowledge and reassemble old knowledge in idiosyncratic ways (Snow & Lohman, 1984).…”
Section: Focus On Specific Training Not Broad Education When Time Amentioning
confidence: 99%
“…Snow and Lohman (1984) suggested that highly able learners thrive on abstract instruction, while less able learners may be best trained by highly structured, concrete demonstrations. Unfortunately, we have not seen consistent ATI patterns as suggested by Snow and Lohman.…”
mentioning
confidence: 99%
“…A highly structured self-development activity represents a less demanding learning environment for learners because learning activities with high structure impose an explicit direction for learning (Snow, 1989). For instance, such activities provide guidance and scaffolding in the form of explicit, sequential learning strategies for the learner to employ throughout the activity (Snow & Lohman, 1984). This externally-provided structure reduces anxiety and self-doubt in regard to one's capability to successfully learn the content of the activity.…”
Section: Self-dissatisfactionmentioning
confidence: 99%
“…The instructional design attributes of content relevancy, learner engagement, challenge, and structure have consistently been acknowledged for their effect on learning, retention, and transfer (e.g., Azevedo & Bernard, 1995;Knowles, 1980;Kraiger, 2003;McCauley et al, 1995;Shute, Gawlick, & Gluck, 1998;Snow & Lohman, 1984;Rigney et al, 1979;Taylor, 1981). Further, these attributes determine the quality of both formal activities and self-development activities (Campbell & Kuncel, 2001;Gagne & Briggs, 1979).…”
Section: Attributes Reflecting High Quality Instructionmentioning
confidence: 99%